Characteristics of primigravid women seeking abortion services at a referral center, Manipur - Devi Ibetombi; Akoijam B; Nabakishore N; Jitendra N; Nonibala Th (Wolters Kluwer Medknow Publications, 2007)
Objective: To explore the characteristics of primigravid women seeking abortion services and find out the reasons for undergoing abortion. Materials and Methods: A cross-sectional study based on data collected in 5 years was carried out. All primigravid women who came to avail of the abortion services were included and their characteristics were recorded. Reasons for undergoing abortion in their first pregnancy were ascertained. The information was gathered by personal interview conducted by a trained person. Results: There were 11,141 MTP cases in the 5 years, with 740 (6.6%) women coming for abortion in their first pregnancy. There was a decrease in these cases during the years under study. Most of the women belonged to the 15-24 years age group. The majority of the women were from rural areas. Abortion services were less sought by women who were educated up to graduation or above. The majority of the women were unmarried. A little more than half of the women sought abortion services with 12 weeks of gestation or more. Parents referred these women for abortion services more than their partners. Sociocultural factor was the commonest reason for undergoing abortion among these women. Conclusion: Pregnancy in unwed girls was the main reason for seeking abortion services. They lack adequate knowledge of contraceptive methods. There is a need for encouraging adolescent health services including sex education.